Comprehensive Analysis of the Role of Artificial Intelligence in General Healthcare and their Impact on General Practices - Alyami, Matared Ali Hamad; AlQhtani, Saeed Mohammad Saeed; Al Garad, Salem Abdullah; Alkustaban, Ahmed Saleh; Aljearh, Mahmoud Nasser Ali; Lesslom, Abdullah Hadi; Al Salah, Abdullah Yahya Ali; Al Alshahi, Ali Yahya; Lesslom, Fahed Hadi Ali; Alajabi, Abdullah Hussain (Journal of Ecohumanism, 2024)
AI has been added to the medical industry, and its presence is beginning to revolutionize how doctors and nurses can practice and improve patients’ health. In this paper, we analyze the use of AI in general healthcare concerning diagnosis, treatment, supervision, and administrative roles. The study also assesses the overall applicability of AI in general medical practice, taking into account the proffered advantages, which are accuracy, less workload, and more efficiency, and the vices, which are data privacy, changes in the workforce, and paucity of regulation. Therefore, using a literature review, the exploration of actual cases, and opinions from healthcare professionals, this paper develops a clear understanding of the status of AI applications and their development prospects in the healthcare industry.